Formation of the children microbiota: its role in overall metabolism - L. A. Dzhaparidzе; O. A. Soldatova (Журнал инфектологии)
Progress in the study of the human microbiome, in terms of its impact on the maintenance of health, is considered as one of the most significant achievements of modern biology and medicine. Studying the bacteria inhabiting the body, understanding the patterns of human interaction with the world of microorganisms, will help to better determine their role in general metabolism, influence on the functioning of various body systems, form a more accurate understanding of the pathogenesis of diseases, become the basis for the prevention of infectious diseases, and the implementation of microbial therapy of infections, obesity, diabetes.The qualitative and quantitative composition of the microbiome, on which the future human health largely depends, affects the mode of birth and the nature and type of nutrition of the newborn.